Transformational Leadership and Employee Performance in the Faculty of Tarbiyah and Teacher Training at UIN Raden Fatah Palembang: Kepemimpinan Transformasional dan Kinerja Pegawai di Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah Palembang - Utami, fajar Tri (Psikologia : Jurnal Psikologi, 2024)
The functioning and success of an organization are influenced by various factors, one of which is the leadership style present within the institution, which in turn affects the performance of the employees within it. Transformational leadership is considered an ideal leadership style and is widely used because it can guide employees. The purpose of this research was to identify the elements that play a role in the Faculty of Tarbiyah and Education at UIN Raden Fatah Palembang, which contribute to the positive impact of transformational leadership on employee performance. The research method used is quantitative descriptive, with a total of 42 participants selected through a saturation sampling method. The results of the hypothesis test show a significance value in both the Kendall version (p is 0.05, sig = 0.058 > 0.05) and the Spearman version (p is 0.05, sig = 0.055 > 0.05), both reaching 0.058. This indicates that there was no correlation between transformational leadership and workplace productivity. The research findings can be used as a reference for institutions in managing their employees' performance.